Piezoelectric laminate and piezoelectric element
The use of a Ta nitride-based lower electrode layer with continuous Ta content change in piezoelectric elements addresses cost and durability issues, achieving superior performance and stability at reduced costs.
Patent Information
- Application Number
- JP2021141804
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-08-31
- Publication Date
- 2025-01-20
- Estimated Expiration
- 2041-08-31
AI Technical Summary
Existing piezoelectric elements using platinum group metals for electrodes are costly due to high material expenses and face challenges in maintaining piezoelectric properties and durability due to oxygen desorption, while alternatives with fewer layers still struggle with manufacturing cost reduction and structural integrity.
A piezoelectric laminate and element with a lower electrode layer containing tantalum (Ta) nitride, where the Ta content changes continuously from the piezoelectric film to the substrate, enhancing conductivity and suppressing oxygen desorption, and optionally incorporating an orientation control layer to stabilize the perovskite structure.
The solution effectively suppresses piezoelectric property deterioration, improves long-term stability, and significantly reduces manufacturing costs by using Ta nitride, maintaining high conductivity and structural integrity without peeling, comparable to platinum group metal performance.
Smart Images

Figure 0007617824000002 
Figure 0007617824000003 
Figure 0007617824000004
Abstract
Description
[Technical field]
[0001] The present disclosure relates to a piezoelectric laminate and a piezoelectric element. [Background technology]
[0002] Perovskite oxides such as lead zirconate titanate (Pb(Zr,Ti)O3, hereafter referred to as PZT) are known as materials with excellent piezoelectric and ferroelectric properties. Piezoelectrics made of perovskite oxides are used as piezoelectric films in piezoelectric elements that have a lower electrode, a piezoelectric film, and an upper electrode on a substrate. These piezoelectric elements are being deployed in a variety of devices, including memories, inkjet heads (actuators), micromirror devices, angular velocity sensors, gyro sensors, ultrasonic elements (PMUT: Piezoelectric Micromachined Ultrasonic Transducers), and vibration power generation devices.
[0003] The piezoelectric properties of perovskite oxides change significantly depending on the excess or deficiency of oxygen in the perovskite structure. In particular, oxygen is easily released from perovskite oxides containing Pb (lead), such as PZT films, and oxygen defects are generated in the piezoelectric film, which tends to cause deterioration in the piezoelectric properties and durability. In order to suppress oxygen release from perovskite oxides, it is effective to use conductive oxides such as SRO (SrRuO3) and IrO2 in the regions of the lower electrode and upper electrode that contact the piezoelectric film. When using a conductive oxide in the region that contacts the piezoelectric film, it is common to stack a precious metal layer such as Pt (platinum) or Ir (iridium) on the conductive oxide layer to ensure good conductivity (see, for example, Patent Document 1).
[0004] Patent Document 2, which relates to a piezoelectric element having a PZT film, proposes that the lower electrode layer be configured so that the conductive oxide is more abundant on the substrate side and the conductive metal is more abundant on the piezoelectric film side in order to improve adhesion at each interface between the substrate and the lower electrode layer, and between the lower electrode layer and the piezoelectric film. It also describes that the conductive metal contained in the lower electrode layer is preferably a Pt group metal.
[0005] On the other hand, Patent Document 3 proposes a piezoelectric element having a first electrode (corresponding to a lower electrode layer) that does not use a Pt group. In Patent Document 3, the lower electrode layer is formed by laminating a first conductive layer, a first intermediate layer made of a nitride compound, a second intermediate layer, and a second conductive layer made of a conductive oxide. Here, the first conductive layer is an alloy of one or more of Ti, Zr, Hf, V, Nb, Ta, Cr, Mo, W, Mn, Fe, Co, Ni, Cu, Ag, and Au, and the second intermediate layer is an alloy of one or more of Ti, Zr, W, Ta, and Al. Patent Document 3 describes that by providing a lower electrode layer having such a laminated structure, it is possible to provide a piezoelectric element having an electrode that is superior in conductivity and durability compared to the case where a platinum group metal is used. [Prior art documents] [Patent documents]
[0006] [Patent Document 1] JP 2018-085478 A [Patent Document 2] JP 2007-300071 A [Patent Document 3] JP 2011-103327 A Summary of the Invention [Problem to be solved by the invention]
[0007] As described in Patent Document 1, in a piezoelectric element having a piezoelectric film of a perovskite oxide, by providing a conductive oxide layer on the piezoelectric film side of the electrode layer, it is possible to suppress the deterioration of the piezoelectric characteristics. Also, as described in Patent Documents 1 and 2, a precious metal of the Pt group is generally used for the lower electrode.
[0008] However, since platinum group metals are very expensive, it is difficult to sufficiently suppress the manufacturing costs of piezoelectric elements having electrodes containing platinum group metals.
[0009] In Patent Document 3, the lower electrode layer does not use platinum group metals, so it can be constructed at a lower cost compared to cases where platinum group metals are used. However, the electrode layer has a structure of at least four layers, and the material costs and manufacturing process are complicated, so the effect of reducing manufacturing costs is still not sufficient.
[0010] The technology disclosed herein has been made in consideration of the above circumstances, and aims to provide a piezoelectric laminate and a piezoelectric element that are capable of suppressing deterioration of piezoelectric characteristics and that can reduce manufacturing costs compared to conventional techniques. [Means for solving the problem]
[0011] The piezoelectric laminate of the present disclosure is a piezoelectric laminate including a lower electrode layer and a piezoelectric film including a perovskite oxide, in this order, on a substrate, The lower electrode layer contains Ta (tantalum) element and contains Ta nitride in the thickness direction at the portion of the lower electrode layer closest to the piezoelectric film in the thickness direction, and includes a region in which the content of Ta element changes in the thickness direction, and the region in which the content of Ta element changes includes a region in which the content of Ta element increases from the piezoelectric film side toward the substrate side, and the change in the content of Ta element in the thickness direction is continuous.
[0012] In the piezoelectric laminate of the present disclosure, it is preferable that the Ta element content in the thickness direction of the lower electrode layer exhibits a maximum value on the substrate side and increases continuously from the piezoelectric film side to the maximum value on the substrate side.
[0013] In the piezoelectric laminate of the present disclosure, the lower electrode layer preferably contains Ta nitride over a range of 20 nm to 60 nm from the piezoelectric film side.
[0014] In the piezoelectric laminate of the present disclosure, it is preferable to provide an orientation control layer containing a metal oxide between the lower electrode layer and the piezoelectric film. In this case, it is preferable that the metal oxide contains at least one of Sr and Ba.
[0015] In the piezoelectric laminate of the present disclosure, the perovskite oxide preferably contains Pb, Zr (zirconium), Ti (titanium) and O (oxygen).
[0016] In the piezoelectric laminate of the present disclosure, the perovskite oxide preferably contains Nb (niobium).
[0017] In the piezoelectric laminate of the present disclosure, the perovskite oxide is preferably a compound represented by the following general formula (1). Pb{(Zr x Ti 1-x ) 1-y Nb y}O3(1) 0 <x<1、0.1≦y≦0.4、
[0018] The piezoelectric element of the present disclosure comprises: and an upper electrode layer provided on the piezoelectric film of the piezoelectric laminate. Effect of the Invention
[0019] According to the piezoelectric laminate and piezoelectric element of the present disclosure, it is possible to suppress the deterioration of the piezoelectric characteristics, and also possible to reduce the manufacturing costs compared to conventional methods. [Brief description of the drawings]
[0020] [Figure 1] 1 is a cross-sectional view showing a layer structure of a piezoelectric laminate and a piezoelectric element according to a first embodiment. [Diagram 2] 2 is a diagram showing profiles of the content of Ta and N elements in the thickness direction of the lower electrode layer in the piezoelectric element shown in FIG. 1. [Diagram 3] 1. FIG. 4 is a diagram showing another profile of the Ta element content in the thickness direction of the lower electrode layer in the piezoelectric element shown in FIG. [Figure 4] 5 is a cross-sectional view showing a layer structure of a piezoelectric laminate and a piezoelectric element according to a second embodiment. FIG. [Diagram 5]13 is a diagram showing the profiles of the content of Ta element and N element in the thickness direction of the lower electrode layer of Example 2. FIG. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0021] Hereinafter, an embodiment of the present invention will be described with reference to the drawings. In the drawings, the thicknesses and ratios of each layer are appropriately changed for ease of viewing, and do not necessarily reflect the actual thicknesses and ratios.
[0022] "Piezoelectric laminate 5 and piezoelectric element 1 according to the first embodiment" Fig. 1 is a cross-sectional schematic diagram showing the layer structure of a piezoelectric stack 5 of a first embodiment and a piezoelectric element 1 including the piezoelectric stack 5. As shown in Fig. 1, the piezoelectric element 1 includes a piezoelectric stack 5 and an upper electrode layer 18. The piezoelectric stack 5 includes a substrate 10, and a lower electrode layer 12 and a piezoelectric film 15 that are laminated on the substrate 10. Here, "lower" and "upper" do not mean up and down in the vertical direction, but simply refer to the electrode disposed on the substrate 10 side across the piezoelectric film 15 as the lower electrode layer 12, and the electrode disposed on the opposite side of the piezoelectric film 15 to the substrate 10 as the upper electrode layer 18.
[0023] In the piezoelectric laminate 5, the lower electrode layer 12 contains Ta element, and contains Ta nitride (TaN) in the portion of the lower electrode layer 12 closest to the piezoelectric film 15 in the thickness direction. Although details will be described later, the lower electrode layer 12 includes a region in which the content of Ta element changes in the thickness direction, and the change in the content of Ta element in the thickness direction is continuous. The change in the content of Ta element in the thickness direction of the lower electrode layer 12 is also continuous. Here, the "content of Ta element in the thickness direction" refers to the ratio of Ta element to all elements at each position in the thickness direction, and is expressed in units of at%. The "thickness direction" refers to the direction perpendicular to the substrate 10. "The change in the content is continuous" means that there is no discontinuous portion in the content profile in the thickness direction (see FIG. 2). Also, "the lower electrode layer 12 contains Ta element" means that the lower electrode layer 12 contains Ta element as a main component that occupies 50 at% or more of the metal elements among the constituent elements that constitute the lower electrode layer 12. In addition, in lower electrode layer 12, it is preferable that the content of elements other than Ta that constitute lower electrode layer 12 and whose content in the entire region of lower electrode layer 12 is 10 at% or more is constant or changes continuously in the thickness direction.
[0024] The enlarged view of FIG. 1 shows a schematic diagram of the change in the Ta element content in the lower electrode layer 12. In the enlarged view of FIG. 1, the greater the Ta element content, the darker the color, and the smaller the content, the lighter the color. FIG. 2 shows the change in the Ta element and N element content in the lower electrode layer 12 in the thickness direction (content profile). The horizontal axis shows the position in the thickness direction of the lower electrode layer 12. 0 on the horizontal axis is the position of the lower electrode layer 12 closest to the piezoelectric film 15 (boundary 12a), and the position of the two-dot chain line is the boundary with the substrate 10.
[0025] In the piezoelectric stack 5 and piezoelectric element 1 of this embodiment, the lower electrode layer 12 includes a first region 12b containing Ta nitride, and a second region 12c made of Ta metal provided on the substrate 10 side of the first region 12b. The first region 12b includes a boundary 12a with the piezoelectric film 15, which is closest to the piezoelectric film 15.
[0026] 2, in this embodiment, the lower electrode layer 12 contains Ta elements throughout the entire thickness direction. The first region 12b is a region in which the content of Ta elements changes in the thickness direction, and the change in the content of Ta elements is primarily increasing from the piezoelectric film 15 side toward the substrate 10 side. More specifically, the content of Ta elements in the first region 12b is a maximum value (here, approximately 100 at%) at the side closest to the substrate 10 in the thickness direction (here, the second region 12c side), and increases monotonically from the boundary 12a, which is closest to the piezoelectric film 15. In the second region 12c, the content of Ta elements is approximately constant in the thickness direction, and is a maximum value (here, approximately 100 at%) continuously from the boundary with the first region 12b. Here, the term "increasing trend" refers to an overall increasing tendency, such as when comparing the starting point and the ending point, the content is higher at the end point than at the starting point, and for example, as shown in Fig. 2, in a content profile with the piezoelectric film 15 side on the left and the substrate 10 side on the right, even if there are some points where the content drops beyond the measurement error, the overall trend is upward to the right, which is included in the increasing trend. Also, "monotonically increasing" refers to an increase in the content profile without including any points where the content drops beyond the measurement error.
[0027] The content of an element in the lower electrode layer 12 can be measured by SIMS (Secondary Ion Mass Spectrometry) analysis, and in this disclosure, the content of an element is a value measured by SIMS. In addition, in actual measurement data, the content fluctuates by about ±5 at % due to noise, so the fluctuation of about ±5 at % is considered to be within the range of measurement error.
[0028] In this embodiment, the lower electrode layer 12 is composed of Ta and N (nitrogen) (but contains unavoidable impurities), and the profile showing the change in the content of N element in the thickness direction of the first region 12b of the lower electrode layer 12 is symmetrical with the profile showing the change in the content of Ta element with respect to the line of 50 at% content as the axis of symmetry. That is, it continuously decreases from the boundary 12a, which is closest to the piezoelectric film 15, toward the second region 12c, and then shows a constant value of approximately 0 at%. Note that the region of the lower electrode layer 12 containing Ta nitride, which is closest to the piezoelectric film 15 (first region 12b in this example), may contain Ta oxynitride (TaON). When the lower electrode layer 12 contains TaON, the profile of N element will naturally differ from that shown in FIG. 2.
[0029] In this embodiment, an example is shown in which almost all of the Ta is nitrided at the boundary 12a between the lower electrode layer 12 and the piezoelectric film 15. However, nitrided Ta and non-nitrided Ta may be mixed at the boundary 12a. However, it is preferable that 20 at% or more of the Ta present at the boundary 12a is nitrided, and more preferably 30 at% or more is nitrided. It is also preferable that 20 at% or more of the Ta element is present as a nitride in the entire first region 12b.
[0030] The thickness t of the lower electrode layer 12 is preferably about 50 nm to 300 nm, and more preferably 100 nm to 300 nm. The lower electrode layer 12 contains Ta nitride at least in the area closest to the piezoelectric film 15, and preferably contains Ta nitride over a range of 20 nm or more from the piezoelectric film 15 side, and more preferably contains Ta nitride over a range of 30 nm or more from the piezoelectric film 15 side. In order to ensure sufficient conductivity without making the thickness t of the lower electrode layer 12 too thick, the range containing Ta nitride is preferably 60 nm or less from the piezoelectric film 15 side. That is, it is preferable that the lower electrode layer 12 contains Ta nitride over a range of 20 nm to 60 nm from the piezoelectric film 15 side, and particularly preferably contains Ta nitride over a range of 40 nm to 60 nm. In this embodiment, the thickness t1 of the first region 12b is preferably 20 nm to 60 nm, more preferably 30 nm to 60 nm, and particularly preferably 40 nm to 60 nm. In the case where the lower electrode layer 12 includes the first region 12b and the second region 12c as in this example, the thickness t2 of the second region 12c is preferably 50 nm to 200 nm, more preferably 80 nm to 150 nm. The thickness of the lower electrode layer 12 can be estimated from a cross-sectional scanning electron microscope (SEM) image, a transmission electron microscope (TEM) or a SIMS (Secondary Ion Mass Spectrometry) analysis. However, since the content of Ta element changes continuously between the region where the content of Ta element changes (here, the first region 12b) and the region where the content of Ta element does not change (here, the second region 12c), the boundary between the two regions is not clear in, for example, a scanning electron microscope image. Therefore, the thicknesses t1 and t2 of the first region 12b and the second region 12c are determined from the composition distribution in the thickness direction of the lower electrode layer 12 (see FIG. 2 and FIG. 5), that is, the measurement data of the content change of the constituent elements.
[0031] The piezoelectric film 15 contains a perovskite oxide. The perovskite oxide preferably accounts for 80 mol % or more of the piezoelectric film 15. Furthermore, the piezoelectric film 15 is preferably made of a perovskite oxide (however, it contains inevitable impurities).
[0032] Perovskite oxides are represented by the general formula ABO3. In the general formula, A is an A-site element and is one or a combination of two or more of Pb, Ba (barium), La (lanthanum), Sr, Bi (bismuth), Li (lithium), Na (sodium), Ca (calcium), Cd (cadmium), Mg (magnesium), and K (potassium). In the general formula, B is a B-site element, and is one or a combination of two or more of Ti, Zr, V (vanadium), Nb, Ta, Cr (chromium), Mo (molybdenum), W (tungsten), Mn (manganese), Fe (iron), Ru, Co (cobalt), Ir, Ni (nickel), Cu (copper), Zn (zinc), Ga (gallium), In, Sn, antimony (Sb), and lanthanide elements. In the general formula, O is oxygen. The standard ratio of A:B:O is 1:1:3, but it may deviate within a range in which a perovskite structure can be formed.
[0033] In particular, the piezoelectric film 15 preferably contains Pb as the main component of the A site. In this specification, the term "main component" means a component that occupies 50 mol % or more. In other words, "containing Pb as the main component of the A site" means that 50 mol % or more of the A site elements are Pb. There are no particular limitations on the elements in the A site other than Pb and the elements in the B site in the Pb-containing perovskite oxide.
[0034] The perovskite oxide is preferably a lead zirconate titanate (PZT) type oxide containing Pb (lead), Zr (zirconium), Ti (titanium) and O (oxygen).
[0035] In particular, the perovskite oxide is preferably a compound represented by the following general formula (P) which contains an additive B1 in the B site of PZT. Pb{(Zr x Ti 1-x ) 1-y B1 y}O3(P) Here, 0 < x < 1 and 0 < y < 0.3. In the general formula (P), Pb: {(Zr x Ti 1+x ) 1-y B y}:O is based on 1:1:3, but may deviate within the range where a perovskite structure can be obtained.
[0036] Examples of B1 include Sc (scandium), V, Nb, Ta, Cr, Mo, W, Mn, Fe, Ru, Co, Ir, Ni, Cu, Zn, Ga, In, Sn, and Sb, etc. It is preferable to contain one or more of these elements. B1 is more preferably any one of Sc, Nb, and Ni.
[0037] In particular, it is preferable that B1 is Nb, the perovskite-type oxide contains Nb, and it is preferably a compound represented by the following general formula (1). Pb{(Zr x Ti 1-x ) 1-y Nb y}O3(1) 0 < x < 1, 0.1 ≤ y ≤ 0.4,
[0038] The film thickness of the piezoelectric film 15 is not particularly limited and is usually 200 nm or more, for example, 0.2 μm to 5 μm. It is preferable that the film thickness of the piezoelectric film 15 is 1 μm or more.
[0039] The substrate 10 is not particularly limited, and examples include substrates such as silicon, glass, stainless steel, yttrium-stabilized zirconia, alumina, sapphire, and silicon carbide. As the substrate 10, a laminated substrate in which a SiO2 oxide film is formed on the surface of a silicon substrate may be used.
[0040] The upper electrode layer 18 is an electrode that is paired with the lower electrode layer 12 and applies a voltage to the piezoelectric film 15. The main component of the upper electrode layer 18 is not particularly limited, and examples thereof include metals or metal oxides such as gold (Au), platinum (Pt), iridium (Ir), ruthenium (Ru), titanium (Ti), molybdenum (Mo), tantalum (Ta), aluminum (Al), copper (Cu), silver (Ag), chromium (Cr), and zinc (Zr), and combinations thereof. In addition, the upper electrode layer 18 may be made of ITO (indium tin oxide), IGZO, LaNiO3, and SRO (which may contain Ba). The upper electrode layer 18 may be a single layer or a laminated structure made of multiple layers. From the viewpoint of suppressing oxygen diffusion from the piezoelectric film 15, it is preferable that at least the region of the upper electrode layer 18 that contacts the piezoelectric film is an oxide electrode.
[0041] The thickness of the upper electrode layer 18 is not particularly limited, but is preferably about 50 nm to 300 nm, and more preferably 100 nm to 300 nm.
[0042] As described above, in the piezoelectric laminate 5 and the piezoelectric element 1 of this embodiment, the lower electrode layer 12 contains Ta element and contains Ta nitride in the region closest to the piezoelectric film 15 in the thickness direction. If the region of the lower electrode layer 12 closest to the piezoelectric film 15 is a metal layer, oxygen in the piezoelectric film 15 may escape and move to the lower electrode layer 12 side, and the metal of the lower electrode layer 12 may be oxidized. In addition, when the piezoelectric film 15 is formed on the lower electrode layer 12, oxygen remaining in the atmosphere may be taken into the surface of the lower electrode layer 12, and the metal of the surface layer of the lower electrode layer 12 may be oxidized. In particular, when the metal is Ta, Ta is oxidized to form Ta2O5, which is an insulator, and the conductivity is significantly reduced. If an insulating layer is formed in the boundary region of the lower electrode layer 12 on the piezoelectric film 15 side, this leads to a decrease in performance as an electrode, which causes a decrease in performance (piezoelectric characteristics) of the piezoelectric element 1. However, the piezoelectric stack 5 and piezoelectric element 1 of this embodiment contain Ta nitride closest to the piezoelectric film 15, so oxidation of Ta is suppressed, and as a result, deterioration of the piezoelectric characteristics can be suppressed. In addition, oxygen elements are less likely to escape from the piezoelectric film 15, which improves long-term stability. Even if Ta nitride is partially oxidized to become Ta oxynitride (TaON), Ta oxynitride is not an insulator, so the deterioration of the function of the lower electrode layer 12 is smaller than when Ta2O5 is formed.
[0043] Furthermore, the lower electrode layer 12 includes a region (here, the first region 12b) in which the content of Ta element changes in the thickness direction, and the change in the content of Ta element in the thickness direction is continuous. If the change in the content of Ta element in the thickness direction is discontinuous, the adhesion may decrease at the discontinuous locations, causing peeling. However, in this embodiment, the change in the content of Ta element in the lower electrode layer 12 is continuous, so that the occurrence of peeling can be suppressed.
[0044] Furthermore, since Ta is used as the metal type of the lower electrode layer 12, costs can be significantly reduced compared to conventional piezoelectric elements that use a Pt group metal as the main component.
[0045] In this embodiment, the content of Ta element in the lower electrode layer 12 increases from the piezoelectric film side to the substrate side. In the region of the lower electrode layer 12 closest to the piezoelectric film 15, the closer the content ratio of Ta and N is to the stoichiometric ratio of TaN of Ta nitride, i.e., 1:1, the higher the effect of suppressing oxidation. On the other hand, the higher the proportion of non-nitrided metal Ta in the lower electrode layer 12, the higher the conductivity and the higher the functionality of the lower electrode layer 12. Therefore, if the content of Ta element increases from the piezoelectric film 15 side to the substrate 10 side as in this embodiment, the effect of suppressing the occurrence of oxygen defects in the piezoelectric film 15 can be improved, and the effect of suppressing the decrease in conductivity can be improved.
[0046] Furthermore, in the piezoelectric stack 5 and piezoelectric element 1 of the above embodiment, in the region where the Ta element content of the lower electrode layer 12 changes, the Ta element content exhibits a maximum value on the side closest to the substrate 10 in the thickness direction, and increases monotonically from the piezoelectric film 15 side. This configuration can enhance the effect of suppressing the migration of oxygen from the piezoelectric film 15 to the lower electrode layer 12 and the effect of suppressing the decrease in electrical conductivity.
[0047] When the lower electrode layer 12 contains Ta nitride over a range of 20 nm to 60 nm from the piezoelectric film 15 side, the effect of suppressing oxygen transfer from the piezoelectric film 15 to the lower electrode layer 12 is further enhanced, and deterioration of the piezoelectric characteristics can be suppressed.
[0048] In the above embodiment, the metal species contained in the lower electrode layer 12 is only Ta, but the lower electrode layer 12 may contain metal species other than Ta. Metal elements other than Ta include Cu, Al, Ti, Ni, Cr, and Fe. The lower electrode layer 12 may also contain C or Si. However, by forming the lower electrode layer 12 only from Ta and N, the number of material species can be reduced and the manufacturing method can be simplified, which is highly effective in reducing costs.
[0049] As described above, in the piezoelectric stack 5 and piezoelectric element 1 of the above embodiment, the lower electrode layer 12 includes the first region 12b in which the Ta element content continuously increases from the piezoelectric film 15 side toward the substrate 10 side, and the second region 12c made of Ta metal, and the change in the Ta element content is as shown in Fig. 2. However, the change in the Ta element content in the thickness direction of the lower electrode layer 12 is not limited to that shown in Fig. 2.
[0050] Fig. 3 shows other examples (profiles a to d) of the change in the Ta element content in the thickness direction of lower electrode layer 12. In Fig. 3, similar to Fig. 2, the horizontal axis indicates the position in the thickness direction of lower electrode layer 12. 0 on the horizontal axis is the position of lower electrode layer 12 closest to piezoelectric film 15 (boundary 12a), and the dashed two-dot line position is the boundary with substrate 10. Although not shown in Fig. 3, the N element profiles are, for example, symmetrical with respect to the Ta element profile and the 50 at % line as the central axis.
[0051] 3, the content of Ta element in the thickness direction of lower electrode layer 12 may be approximately 50 at % at boundary 12a with piezoelectric film 15, gradually increase toward substrate 10, reach a maximum value, and then decrease toward substrate 10. In profile a, the content of Ta element changes over the entire thickness direction.
[0052] 3, the Ta element content in the thickness direction of lower electrode layer 12 may be approximately 50 at % at boundary 12a with piezoelectric film 15, show a constant value for a while from boundary 12a toward substrate 10, and then monotonically increase toward substrate 10 to reach a maximum value. In profile b, the range of monotonous increase is the region where the Ta element content changes.
[0053] In the above-described embodiment and profiles a and b, the content of Ta element is approximately 50 at% at the part of lower electrode layer 12 closest to piezoelectric film 15. When lower electrode layer 12 is composed of Ta and N, if Ta element is completely nitrided at boundary 12a on the piezoelectric film 15 side, the content of Ta element is 50 at% and the content of N is 50 at%. In this case, since there is no unnitrified Ta element, the effect of suppressing oxidation by oxygen in piezoelectric film 15 is high.
[0054] However, as shown in profile c of Fig. 3, the Ta element content at boundary 12a of lower electrode layer 12 closest to piezoelectric film 15 is not limited to 50 at% and may be greater than 50 at%. Also, as shown in profile c of Fig. 3, the Ta element content may increase continuously from the closest to piezoelectric film 15 toward the substrate 10 throughout the entire thickness direction of lower electrode layer 12. Furthermore, as shown in profile d of Fig. 3, the Ta element content may decrease from the closest to piezoelectric film 15 toward the substrate 10 throughout the entire thickness direction of lower electrode layer 12.
[0055] In any of the profiles a to d, the lower electrode layer 12 contains Ta element and contains Ta nitride in the side closest to the piezoelectric film 15 in the thickness direction of the lower electrode layer 12. In addition, in the thickness direction, a region in which the content of Ta element changes is included, and the change in the content of Ta element in the thickness direction is continuous. In any of the cases, since Ta nitride is included in the side closest to the piezoelectric film 15, oxidation is suppressed and the deterioration of the piezoelectric characteristics can be suppressed. In addition, since oxygen element is less likely to escape from the piezoelectric film 15, the effect of improving long-term stability can be obtained. And, since the change in the content of Ta element in the lower electrode layer 12 is continuous, the occurrence of peeling can be suppressed. Furthermore, since Ta is used as the metal species of the lower electrode layer 12, the cost can be reduced compared to conventional piezoelectric elements that use Pt group metals as the main component.
[0056] In addition, for profiles a to c, the content of Ta element increases in the thickness direction, so that the effect of suppressing oxygen on the piezoelectric film side is obtained, and the effect of suppressing the decrease in electrical conductivity is also obtained.
[0057] "Piezoelectric laminate 5A and piezoelectric element 1A according to the second embodiment" Fig. 4 is a schematic cross-sectional view of a piezoelectric laminate 5A according to the second embodiment and a piezoelectric element 1A including the piezoelectric laminate 5A. In Fig. 4, the same components as those of the piezoelectric laminate 5 and the piezoelectric element 1 according to the first embodiment shown in Fig. 1 are denoted by the same reference numerals and detailed description thereof will be omitted.
[0058] 4, the piezoelectric stack 5A and the piezoelectric element 1A include an adhesion layer 11 between a substrate 10 and a lower electrode layer 12. In addition, an orientation control layer 13 is included between the lower electrode layer 12 and a piezoelectric film 15.
[0059] The adhesion layer 11 is provided to improve adhesion between the substrate 10 and the lower electrode layer 12 and to suppress peeling. The adhesion layer 11 is preferably made of Ti, W, TiW, or the like.
[0060] The orientation control layer 13 is formed on the lower electrode layer 12. The orientation control layer 13 is a layer provided to suppress the occurrence of a pyrochlore phase that is likely to form in the initial stage of film formation of the piezoelectric film 15 and to obtain a good perovskite-type oxide. The orientation control layer 13 contains a metal oxide. The metal oxide preferably contains at least one of Sr and Ba.
[0061] In addition, as the orientation control layer 13, it is preferable to use a growth control layer described in, for example, WO 2020 / 250591, WO 2020 / 250632, and JP 2020-202327 A. That is, the orientation control layer 13 preferably contains a metal oxide represented by the following general formula (2). Ma d Mb 1-d O e (2) Ma is one or more metal elements that can substitute for the A site of a perovskite oxide, Mb consists of metal species that can be substituted at the B site of the perovskite-type oxide, with one of Sc, Zr, V, Ta, Cr, Mo, W, Mn, Fe, Ru, Co, Ir, Ni, Cu, Zn, Cd, Ga, In, and Sb as the main component, O is an oxygen element. Here, d and e represent the composition ratios respectively, where 0 < d < 1, and e varies depending on the valences of Ma and Mb.
[0062] Specific orientation control layers 13 include BaRuO3 and SrRuO3, etc.
[0063] The thickness of the orientation control layer 13 is preferably 2 nm or more and 20 nm or less, and more preferably about 10 nm.
[0064] Also in the piezoelectric laminate 5A and the piezoelectric element 1A of this embodiment, the configuration of the lower electrode layer 12 is the same as that of the piezoelectric laminate 5 and the piezoelectric element 1 of the first embodiment. That is, the lower electrode layer 12 contains Ta element, contains Ta nitride on the side closest to the piezoelectric film 15 in the thickness direction of the lower electrode layer 12, contains a region where the content of Ta element changes in the thickness direction, and the change in the content of Ta element in the thickness direction is continuous. Since Ta nitride is contained on the side closest to the piezoelectric film 15, oxidation is suppressed, and a decrease in piezoelectric characteristics can be suppressed. Also, since it becomes difficult for oxygen element to escape from the piezoelectric film 15, an effect of improving long-term stability can be obtained. Since the change in the content of Ta element in the lower electrode layer 12 is continuous, the occurrence of peeling can be suppressed. Furthermore, since Ta is used as the metal species of the lower electrode layer 12, the cost can be suppressed compared with the conventional piezoelectric element using a metal of the Pt group as the main component.
[0065] Furthermore, the piezoelectric laminate 5A and piezoelectric element 1A of this embodiment are provided with the orientation control layer 13, and the piezoelectric film 15 is formed on the orientation control layer 13, so that it is possible to suppress the occurrence of the pyrochlore phase that is likely to form in the early stages of film formation. Since it is possible to suppress the occurrence of the pyrochlore phase at the interface of the piezoelectric film 15 on the lower electrode layer 12 side, the piezoelectric properties of the piezoelectric film 15 are good, and it is possible to obtain a higher dielectric constant and a higher piezoelectric constant than when the orientation control layer 13 is not present.
[0066] The piezoelectric elements 1, 1A or piezoelectric laminates 5, 5A in the above-described embodiments are applicable to ultrasonic devices, mirror devices, sensors, memories, and the like. EXAMPLES
[0067] Hereinafter, specific examples and comparative examples of the piezoelectric element of the present disclosure will be described. First, the method of manufacturing the piezoelectric element of each example will be described. Note that the conditions other than the configuration of the lower electrode layer and the presence or absence of the orientation control layer were the same for each example. In addition, an RF (Radio frequency) sputtering device was used to deposit each layer.
[0068] (Production method) -substrate- A 6-inch silicon wafer with a thermal oxide film was used as the substrate.
[0069] -Lower electrode layer- A lower electrode layer was formed on the thermal oxide film of the substrate. The film formation conditions for the lower electrode layer in each example were as follows. The back pressure [Pa] and film formation temperature in each example were as shown in Table 1.
[0070] [Reference example] Before forming the lower electrode layer, a 20 nm thick TiW film was formed on the thermal oxide film of the substrate as an adhesive layer. Then, a 150 nm thick Ir film was formed on the TiW layer as the lower electrode layer under the conditions of Ar gas 60 sccm, RF power 300 W, and film formation pressure 0.25 Pa.
[0071] [Comparative Example 1] A Ta film was formed to a thickness of 150 nm on the thermal oxide film of the substrate under conditions of Ar gas 60 sccm, RF power 300 W, and film formation pressure 0.25 Pa. In Comparative Example 1, the lower electrode layer was a single layer of Ta metal layer.
[0072] [Comparative Example 2] A 100 nm thick Ta film was formed on the thermal oxide film of the substrate under conditions of Ar gas 60 sccm, RF power 300 W, and film formation pressure 0.25 Pa. Subsequently, a 50 nm thick Ta nitride film was formed on the Ta layer under conditions of Ar gas 30 sccm, N2 gas 30 sccm, RF power 300 W, and film formation pressure 0.25 Pa. That is, in Comparative Example 2, the lower electrode layer had a two-layer structure of a Ta metal layer and a Ta nitride layer of a fixed composition provided thereon.
[0073] [Examples 1 to 6] A Ta film was formed to a thickness of 100 nm under the conditions of Ar gas 60 sccm, RF power 300 W, and film formation pressure 0.25 Pa. Subsequently, the Ar gas was gradually reduced from 60 sccm to 30 sccm, and N2 gas was gradually increased from 0 sccm to 30 sccm at the same time, while a Ta nitride film was formed to the thickness shown in Table 1 for each example under the conditions of RF power 300 W and film formation pressure 0.25 Pa. By continuously changing the flow rates of Ar gas and N2 gas after the Ta metal layer is formed to form a Ta nitride film, it is possible to form a Ta nitride layer in which the Ta element content gradually increases and the N element content gradually decreases from the surface toward the metal layer (see FIG. 5). That is, in Examples 1 to 6, the lower electrode layer had a laminated structure of a Ta metal layer (second region in the embodiment) and a composition gradient layer (first region in the embodiment) in which the Ta element content and the N element amount gradually change. In Table 1, the order of the first region / second region is described in the item of the layer configuration of the lower electrode layer. In Table 1, TaN (gradient 50 nm) indicates that the first region is an oxynitride, and is a gradient layer with a thickness of 50 nm. Between the Ta metal layer and the composition gradient layer and in the composition gradient layer, the content of Ta element changes continuously, and a seamless bottom electrode layer was obtained.
[0074] -Orientation control layer- In Example 3, Ar was flowed on the lower electrode layer so that the substrate temperature was 500° C. and the deposition pressure was 0.8 Pa, and a BaRuO 3 film was deposited to a thickness of 10 nm as the orientation control layer. In Example 4, Ar was flowed on the lower electrode layer so that the substrate temperature was 500° C. and the deposition pressure was 0.8 Pa, and a 10 nm SrRuO 3 film was formed as an orientation control layer. The other examples, reference examples and comparative examples did not include an orientation control layer.
[0075] -Piezoelectric film- On the lower electrode layer or the orientation control layer, a Nb-doped PZT film was deposited as a piezoelectric film to a thickness of 2 μm by RF (Radio Frequency) sputtering. The substrate temperature during deposition was 550°C, and the sputtering gas had a flow rate ratio of O2 gas to Ar gas of 3%. The RF power was 1 kW.
[0076] As described above, a laminate substrate was obtained in which a lower electrode and a piezoelectric film were laminated on a substrate. For each of the laminate substrates in the examples and comparative examples, a diffraction pattern was obtained by X-ray diffraction using an X-ray diffraction device manufactured by Malvern Panalytical, and it was confirmed that the piezoelectric film had a perovskite structure.
[0077] -Top electrode layer- An ITO layer having a thickness of 100 nm was formed by sputtering on the piezoelectric film of the above-mentioned laminated substrate.
[0078] <Lower electrode layer element distribution measurement> The element distribution in the thickness direction of the lower electrode layer can be measured by SIMS (Secondary Ion Mass Spectrometry) analysis. As an example, data obtained by SIMS analysis using a sample having the lower electrode layer of Example 2 is shown in FIG. 5. The sample was subjected to Ar + The analysis was carried out while cutting the Ta nitride layer from the surface side by ion irradiation.
[0079] In FIG. 5, the horizontal axis indicates the position in the thickness direction of the lower electrode layer, with 0 being the surface position of the lower electrode layer, and the position to the right of the horizontal axis is closer to the substrate. As shown in FIG. 5, at the surface position of the lower electrode layer, the contents of both Ta and N were close to 50 at%. The content of Ta gradually increased from the surface toward the substrate side, and reached approximately 100 at% at about 50 nm, showing a constant value. On the other hand, the content of N gradually decreased from the surface toward the substrate side, and reached approximately 0 at% at about 50 nm, showing a constant value. It is clear that the lower electrode layer of Example 2 can obtain a layer showing a profile in which the contents of Ta and N gradually change in the thickness direction, as shown in FIG. 5, by gradually changing the flow rate ratio of Ar gas and N2 gas during the formation of the gradient layer.
[0080] <Measurement of dielectric constant> (Preparation of measurement samples) The laminated substrate was diced into 1-inch (25 mm) squares to produce 1-inch square piezoelectric laminates. When forming the upper electrode layer, a metal mask with a partial circular opening of 400 μm in diameter was used to form a circular upper electrode layer of 400 μm in diameter. A 1-inch square with a circular upper electrode layer in the center was then cut out to prepare a sample for measuring the dielectric constant.
[0081] (measurement) The dielectric constant was measured using an impedance analyzer manufactured by Agilent. An AC voltage with a frequency of 1 kHz was applied to the piezoelectric element of each example, and the dielectric constant was calculated from the measured impedance value. The obtained dielectric constants are shown in Table 1.
[0082] <Measurement of piezoelectric constant> (Preparation of measurement samples) A cantilever was fabricated by cutting a rectangular piece measuring 2 mm x 25 mm from the laminated substrate.
[0083] (measurement) The piezoelectric constant was measured using a cantilever according to the method described in I. Kanno et. al. Sensor and Actuator A 107 (2003) 68., with an applied voltage of a sine wave of -10 V ± 10 V, i.e., a bias voltage of -10 V and an applied voltage of a sine wave with an amplitude of 10 V. The measurement results are shown in Table 1.
[0084] The piezoelectric element configuration and evaluation of each example are summarized in Table 1. The reference example is a piezoelectric element having a lower electrode layer made of Ir, which has been conventionally used, and is an example with good dielectric constant and piezoelectric constant. Table 1 also lists the ratio of the dielectric constant and piezoelectric constant of each example and comparative example to the value of the reference example.
[0085] [Table 1]
[0086] When the lower electrode layer is a Ta metal layer as in Comparative Example 1, the dielectric constant is 20% lower and the piezoelectric constant is 15% lower than in the reference example having an Ir metal layer as the lower electrode layer. Comparative Example 2 has a second region made of Ta and a first region made of Ta nitride as the lower electrode layer, and the first region has a substantially constant composition in the thickness direction. Therefore, in Comparative Example 2, the content of Ta element is discontinuous at the boundary between the first region and the second region. In the element of Comparative Example 2, peeling occurred, and the dielectric constant and piezoelectric constant could not be measured.
[0087] The dielectric constant and piezoelectric constant of the piezoelectric elements of Examples 1 to 6 could be measured without peeling, which is believed to be because the Ta element content changes continuously in the thickness direction of the lower electrode layer.
[0088] The piezoelectric elements of Examples 1 to 6 have a dielectric constant and a piezoelectric constant that are lower by 5% or less than those of the reference example, and it is clear that they have good dielectric constants and piezoelectric constants. In particular, in Examples 3 and 4, which are provided with an orientation control layer, it was possible to obtain a dielectric constant and a piezoelectric constant that are comparable to those of the piezoelectric element provided with an Ir electrode layer. In Examples 1 to 6, only Ta is used as the metal species in the lower electrode layer, and the material cost can be significantly reduced compared to the conventional piezoelectric element using Ir. As shown in Examples 1 to 6, it is clear that the technology of the present disclosure can provide a piezoelectric element that exhibits piezoelectric characteristics that are comparable to those of the conventional piezoelectric element using Ir in the lower electrode layer, and that can significantly reduce the manufacturing cost. [Explanation of symbols]
[0089] 1. 1A piezoelectric element 5, 5A Piezoelectric laminate 10 Substrate 11 Adhesion layer 12 Lower electrode layer 12a Boundary of the lower electrode layer on the piezoelectric film side 12b 1st area 12c 2nd area 13 Orientation control layer 15 Piezoelectric film 18 Upper electrode layer
Claims
1. A piezoelectric laminate including a lower electrode layer and a piezoelectric film including a perovskite oxide, in this order, on a substrate, The lower electrode layer contains Ta. the lower electrode layer includes a tantalum nitride closest to the piezoelectric film in a thickness direction; Further, the thickness direction includes a region in which the content of the Ta element changes, and the change in the content of the Ta element in the thickness direction is continuous, a piezoelectric laminate, in which the content of the Ta element in the region is maximum at a portion closest to the substrate in the thickness direction, and increases monotonically from the piezoelectric film side.
2. The piezoelectric laminate according to claim 1 , wherein the Ta element content changes in a manner that increases from the piezoelectric film side toward the substrate side.
3. 3. The piezoelectric stack according to claim 1, wherein the lower electrode layer contains the Ta nitride over a range of 20 nm to 60 nm from the closest to the piezoelectric film.
4. The piezoelectric laminate according to claim 1 , further comprising an orientation control layer containing a metal oxide between the lower electrode layer and the piezoelectric film.
5. The piezoelectric stack of claim 4 , wherein the metal oxide comprises at least one of Sr and Ba.
6. The piezoelectric stack according to claim 1 , wherein the perovskite oxide contains Pb, Zr, Ti and O.
7. The piezoelectric stack according to claim 6 , wherein the perovskite oxide contains Nb.
8. The perovskite oxide is a compound represented by the following general formula (1): Pb{(Zr x Ti 1-x )1-yNb y }O 3 (1) 0<x<1, 0.1≦y≦0.4, The piezoelectric laminate according to claim 7.
9. A piezoelectric laminate according to any one of claims 1 to 8; an upper electrode layer provided on the piezoelectric film of the piezoelectric laminate.
Citation Information
Patent Citations
Piezoelectric actuator
JP2000015809A
Piezoelectric element and manufacturing method thereof, electronic device, ink jet device
JP2007300071A
Piezoelectric element, piezoelectric actuator, liquid injection head, and liquid injection device
JP2011103327A
Piezoelectric element, piezoelectric actuator, droplet jetting head, droplet injection device, and method of manufacturing piezoelectric element
JP2011192887A
Piezoelectric film and piezoelectric element
JP2012009677A